Karl der Kühne (1433-1477) : Kunst, Krieg und Hofkultur - Marti, Susan; Bernisches historisches Museum; Ausstellung. Bern. Historisches Museum Bern. 2008-04, 25; Tentoonstelling. Brugge. Bruggemuseum & Groeningemuseum. 2009-03, 27 (Bern : Historisches Museum, 2008)
Trad. française: Charles le Téméraire (1433-1477).
25.04.2008 - 24.08.2008 (Bern)
27.03.2009 - 21.07.2009 (Brugge)
boek
Keywords: Karel de Stoute, -- hertog van Bourgondië